NECESSITY OF THE STATE FOSTERAGE IN THE MILITARIZED EDUCATIONAL INSTITUTIONS - Indriksons, Alens (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Due to today's complex and changing geopolitical situation in the State Border Guard College as one of the militarized educational institutions it is important to promote the student's understanding of values and virtues, enrich their historical and cultural experience, strengthen their patriotism, belonging and loyalty to the constitution and to the Republic of Latvia. Patriotism can’t be defined because it varies according to the subject's position. It is not a specific ideology, but this is a love of native land and defending it in words and in works. Patriotism means to love own country not just idolize the state symbols. Aim of the study is to clarify and scientifically substantiate the necessity of introducing the study subject “State Fosterage” into studies of border guards at the State Border Guard College as one of the militarized educational institutions and to determine the development of students' statehood consciousness, loyalty and patriotism as one of the study programs objectives at the State Border Guard College. For this purpose analysis and evaluation of documents, scientific, pedagogical and psychological literature were performed and conclusions about the necessity of introduction of the State Fosterage subject and possibilities of patriotism development were summarized.